EUS-guided gallbladder drainage vs dual stent transpapillary gallbladder drainage for management of acute cholecystitis - Amin, Dhruval; Cooper, Katherine M.; Rau, Prashanth; Sayegh, Lea; Mostafa, Nouran; Achebe, Ikechukwu; DeVore, Zachary; Gonzalez, Daniella; Stephanie, Stephanie; Zivny, Jaroslav; Mehta, Savant; Marshall, Christopher; Nasser-Ghodsi, Navine; Storm, Andrew C; Marya, Neil B. (Endoscopy International Open, 2025)
Cholecystectomy (CCY) is the standard treatment for acute cholecystitis. For non-surgical patients, percutaneous cholecystostomy tube (PT-GBD) is recommended but is associated with high readmission rates and poor quality of life. Endoscopic gallbladder decompression techniques, including endoscopic transpapillary gallbladder drainage (ET-GBD) and endoscopic ultrasound-guided gallbladder drainage (EUS-GBD), are alternatives. Studies comparing ET-GBD and EUS-GBD have shown EUS-GBD to have superior outcomes. However, these studies assessed ET-GBD mostly via single transcystic stent placement (SSET-GBD). This study aimed to compare outcomes of dual transcystic stents (DSET-GBD) and EUS-GBD in non-surgical candidates with acute cholecystitis.A multicenter analysis was conducted on patients who underwent ET-GBD or EUS-GBD between January 2019 and January 2023. Data were extracted from electronic medical records and outcomes including technical success, success, adverse events (AEs), and recurrence rates of cholecystitis were measured.Of 129 procedures (56 EUS-GBD; 73 ET-GBD), technical success was achieved in 87.5% of EUS-GBD and 86.3% of ET-GBD attempts. Immediate clinical success was achieved in 98.1% for EUS-GBD and 100% for DSET-GBD. AE rates were similar between the groups. Recurrent cholecystitis rates were 5.3% for EUS-GBD and 8.2% for DSET-GBD (P = 0.692).This study demonstrates that DSET-GBD has similarly low rates of recurrent acute cholecystitis compared with EUS-GBD. DSET-GBD should be considered as an alternative management strategy for management of acute cholecystitis in patients who are unable to undergo CCY.
Keywords: Endoscopic ultrasonography; Pancreatobiliary (ERCP/PTCD); ERC topics; Intervention EUS